Smartphone ophthalmoscope as a tool in teaching direct ophthalmoscopy: a crossover randomized controlled trial - Hongxi Wang; Xulong Liao; Mingzhi Zhang; Chi Pui Pang; Haoyu Chen (Medical Education Online, 2023)
ABSTRACTTo evaluate the effectiveness of smartphone ophthalmoscope (SO) in teaching ophthalmoscopy, compared with direct ophthalmoscope (DO). In this cross-over study, 45 final-year medical students attending sessions at a single institution were randomly allocated to two groups (A and B). Both groups attended two training sessions. In the first session, Group A students were taught ophthalmoscopy using DO and Group B students using SO. In the second session, the training sessions were crossed over. A series of eye models with 10 letters placed on the inner surface were designed to assess the students’ skill on ophthalmoscopy. Students performed ophthalmoscopy on the eye models, recorded their findings, and completed a questionnaire of feedback on DO and SO. The main outcome measure was the score of ophthalmoscopy, assessed by the student correctly recording each letter (score 1 for each letter). For Group A, the mean score of ophthalmoscopy on the eye model using DO and SO was 3.9±2.4 and 8.2±2.2, respectively. For Group B, the mean score of ophthalmoscopy on the eye model using SO and DO 8.7±1.8 and 5.7±3.5 . Students scored significantly higher in ophthalmoscopy when using SO than DO (P<0.001). They expressed better visualization of the fundus using SO than DO (4.49±0.65 vs 4.13±0.81, P=0.004). Students’ performance of ophthalmoscopy was better when SO was used compared with DO. The use of SO as an adjunctive tool is recommended to improve the effectiveness of teaching ophthalmoscopy.